Alisol A 24-Acetate and Alisol B 23-Acetate Induced Autophagy Mediates Apoptosis and Nephrotoxicity in Human Renal Proximal Tubular Cells - Wang, Chunfei; Feng, Liang; Ma, Liang; Chen, Haifeng; Tan, Xiaobin; Hou, Xuefeng; Song, Jie; Cui, Li; Liu, Dan; Chen, Juan; Yang, Nan; Wang, Jing; et al. (Frontiers in Pharmacology, 2017)
Two natural compounds alisol A 24-acetate (24A) and alisol B 23-acetate (23B) are abundant in Rhizoma alismatis. In the present study, we evaluated the induction of 24A and 23B on apoptosis and possible nephrotoxicity of human renal proximal tubular (HK-2) cells by activating autophagy and also explored its regulation on PI3K/Akt/mTOR signaling pathway. Presently, Clusterin, Kim-1, and TFF-3 were considered to be new bioindicators of nephrotoxicity. Interestingly, the protein expression and mRNA levels of Clusterin, Kim-1 and TFF-3 could be significantly increased by 23B and 24A in vivo and in vitro. Furthermore, cell apoptosis could be triggered by 23B and 24A via significantly decreasing the protein expression and mRNA levels of Bcl-2 and Bcl-xl. Autophagy of HK-2 cells could be induced by both 23B and 24A via significantly enhancing the ratio of LC3II/LC3I, the protein expression of Beclin-1 as well as the mRNA levels of LC3 and Beclin-1. Meanwhile, PI3K/Akt/mTOR signaling pathway could be inhibited by these two compounds. An autophagy inhibitor, 3-methyladenine, could partially reverse cell viability and conversely change the ratio of LC3II/LC3I and the protein expression of Bcl-2 and Kim-1. Thus this study helped to understand that 23B and 24A induced autophagy resulted in apoptosis and nephrotoxicity through inhibiting PI3K/Akt/mTOR signaling pathway, facilitating further studies for nephrotoxicity induced by these two compounds and could be beneficial for safe use of Rhizoma alismatis in clinic.